Regional Studies of Environmental Management Risks under the Conditions of Modern Climate Change: Basic Approaches and Assessment Methods - Nevidimova O. G. Olga Gennadjevna; Volkova E. S. Elena Sergeevna; Melnik M. A. Mariya Alekseevna; Yankovich E. P. Elena Petrovna (2022, 2022)
Title screen